Is too much personal dread stifling alternative pathways to improving urban water security?. (1st July 2020) - Kosovac, Anna; Davidson, Brian
Abstract: Despite an ongoing dire prognosis of the state of water resources, water practitioners maintain their traditional approaches to water planning. Alternative water projects to those that are considered 'business-as-usual' are not contemplated despite the threats posed by increasing urbanisation and climate change. Previous studies in psychological perceptions of risk in other fields have found that the personal feelings of risk practitioners, particularly feelings of dread, have had a significant impact on risk perceptions, an element known to be affecting decision-making of an individual. Could a similar trend exist in the water sector? We consider the decision-making process of 77 water practitioners in Melbourne Australia, to determine their personal biases and attitudes towards these alternative water pathways. In particular, this study assesses the impact of cognitive bias on reported risk scores in the water sector. Utilising pre-validated risk psychology survey methodology ( Slovic et al, 1985), psychometric testing was conducted to determine the influences that guide their personal risk perceptions, and in turn, their decision-making processes. It was concluded that 'Dread' plays a key role in the variation of risk scores between the participants that were evaluated. Furthermore, variables such as 'Fear of the Unknown' and 'Dread related to perceived fatal risk' where also found to be statistically significant factors in the link between risk scores and cognitive bias. These findings are critical in water planning, as a feeling of dread may be driving up risk scores, thus reducing the chances of establishing alternative water projects. Highlights: Psychological bias occurs in the risk assessments of water projects. Dread was found to be an important psychological factor increasing risk scores for unfamiliar and new water projects. Higher risk scores result in water projects not being pursued. Personal affect of water practitioners changes investment outcomes in the options analysis of water projects.